Three-dimensional Inkjet Printed Solid Oxide Electrochemical Reactors.I. Yttria-stabilized zirconia Electrolyte - Kleiminger,L; Farandos,N; Li,T; Hankin,A; Kelsall,GH (Electrochimica Acta, 2016)
Solid oxide fuel cell (SOFC) and electrolyser (SOE) performances can be enhanced significantly by increasing the densities of (electrode | electrolyte | pore) triple phase boundaries and improving geometric reproducibility and control over composite electrode | electrolyte microstructures, thereby also aiding predictive performance modelling. We developed stable aqueous colloidal dispersions of yttria-stabilized zirconia (YSZ), a common SOFC electrolyte material, and used them to fabricate 2D planar and highly-customisable 3D microstructures by inkjet printing. The effects of solids fraction, particle size, and binder concentration on structures were investigated, and crack-free, non-porous electrolyte planes were obtained by tailoring particle size and minimising binder concentration. Micro-pillar arrays and square lattices were printed with the optimised ink composition, and a minimum feature size of 35 μm was achieved in sintered structures, the smallest published to-date. YSZ particles were printed and sintered to a 23 μm thick planar electrolyte in a Ni-YSZ|YSZ|YSZ-LSM|LSM electrolyser for CO2 splitting; a feed of 9:1 CO2:CO mixture at 1.5 V and 809 °C produced a current density of −0.78 A cm−2 even without more complex 3D electrode | electrolyte geometries.